2004
DOI: 10.1158/0008-5472.can-04-1446
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 and Notch2 Have Opposite Effects on Embryonal Brain Tumor Growth

Abstract: The role of Notch signaling in tumorigenesis can vary; Notch1 acts as an oncogene in some neoplasms, and a tumor suppressor in others. Here, we show that different Notch receptors can have opposite effects in a single tumor type. Expression of truncated, constitutively active Notch1 or Notch2 in embryonal brain tumor cell lines caused antagonistic effects on tumor growth. Cell proliferation, soft agar colony formation, and xenograft growth were all promoted by Notch2 and inhibited by Notch1. We also found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
301
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(320 citation statements)
references
References 40 publications
(38 reference statements)
13
301
1
1
Order By: Relevance
“…Very recently, Balint et al (2005) also demonstrated that activation of Notch1 pathway could promote melanoma progression. These data suggested that activation of both Notch1 and 2 receptors could be oncogenic in melanoma cells; however, it should also be noted that Notch1 and 2 can play an opposite role in tumorigenesis in a single tumor cell type (Fan et al, 2004;Parr et al, 2004). In the present study, we could not find any significant differences in the expression of the Notch receptor and ligand between the skeletrophin-positive and -negative melanoma cells tested.…”
Section: Discussioncontrasting
confidence: 65%
“…Very recently, Balint et al (2005) also demonstrated that activation of Notch1 pathway could promote melanoma progression. These data suggested that activation of both Notch1 and 2 receptors could be oncogenic in melanoma cells; however, it should also be noted that Notch1 and 2 can play an opposite role in tumorigenesis in a single tumor cell type (Fan et al, 2004;Parr et al, 2004). In the present study, we could not find any significant differences in the expression of the Notch receptor and ligand between the skeletrophin-positive and -negative melanoma cells tested.…”
Section: Discussioncontrasting
confidence: 65%
“…The oncogenic potential of Notch-1 has been shown in T-cell leukemia in which the truncated form of Notch-1 is expressed (Ellisen et al, 1991). On the other hand, Notch1 can cause growth arrest in medulloblastomas, mammalian skin tumors, and small-cell lung cancers (Sriuranpong et al, 2001;Nicolas et al, 2003;Fan et al, 2004). DLK1 is a negative regulator of Notch1 activation and decreases expression of Hes-1 (a downstream target of Notch-1) in 3T3-L1 fibroblasts (Baladron et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activities of Notch1ICD, Notch2-ICD and Notch3ICD were markedly different from each other, and the activities of Notch1ICD or Notch3ICD were reduced by coexpression of Notch2ICD. Fan et al (2004) also showed that Notch1ICD and Notch2ICD can have opposite effects on the growth of a single tumor type. Moreover, Notch1 acts as an oncogene in some carcinomas (Capobianco et al, 1997;Weijzen et al, 2002;Kiaris et al, 2004), and as a tumor suppressor (Nicolas et al, 2003;Fan et al, 2004) in others.…”
Section: Effect Of Notch On Tgf-b Signaling During Mammary Developmenmentioning
confidence: 93%